Planning Capacity Requirements for Spiral Pipe Production Time with Capacity Requirement Planning (CRP) Method at A Pipe Production Company in Sidoarjo - Rusindiyanto; Rizqi Novita Sari (Nusantara Science and Technology Proceedings, 2022)
Company resources that are less effective and efficient cause problems in the production planning of PT. X, a company engaged in manufacturing spiral pipes, often experiences time delays in the spiral pipe production process due to a large number of requests, so the fulfillment of consumer demands is hampered. To overcome these problems, this research was conducted using the Capacity Requirement Planning (CRP) method so that companies can plan and implement arrival rates to adjust orders according to the available time capacity and identify work center areas where the production process is faster. The data processing that has been carried out shows different results between the company's methods, namely getting a total lack of time capacity of 549.77 hours, while the CRP method gets a total lack of time capacity of 288.2 hours so the CRP method is considered better because of the total shortage of time capacity. produced is smaller than the company's previous method.